For the Sake of Making Molecules - Antonio Togni (CHIMIA, 2023)
The aim of this article, while reviewing part of my research activities, is to illustrate the somewhat chaotic way leading from one specific topic to another – from e.g. ferrocenyl ligands for asymmetric catalysis, to asymmetric fluorination, to reagents for perfluoroalkylation, just to mention some of the most fruitful ones. That the way meandering  through several areas of research in chemical synthesis can be described as chaotic is not primarily due to my inability to plan the work of my research group. In the contrary, it is argued that academic research, viewed as mean to educating and forming young researchers, should resist the temptation towards an increasing projectification, milestone mentality, the myth of societal relevance, and consciously aim for a more anarchical trait, much in the sense of Feyerabend’s “anything goes”.